New treatment approaches in melanoma: current research and clinical prospects. - Rughani, MG; Gupta, A; Middleton, MR (2013)
Ipilimumab and vemurafenib have changed the clinical landscape in melanoma. Both drugs offer effective treatment for metastatic melanoma, but with limitations. Ipilimumab benefits only a minority of those treated, with no means to identify them prospectively. The efficacy of vemurafenib is tied to the presence of an activating mutation in BRAF, and so is more predictable. However, acquired resistance develops within months. As we understand these, and similar, agents better, the means to select patients for treatment, to increase the duration of response and to identify the best stage at which to intervene will lead to improved outcomes for patients. Several trials are already under way or being developed to build upon these exciting discoveries.